Health Weaver Mobile: Designing a Mobile Tool for Managing Personal Health Information during Cancer Care - Klasnja, Predrag (American Medical Informatics Association, 2010)
Cancer patients manage a great deal of information to coordinate their care. Critical aspects of this work take place while patients are away from home or have diminished attention due to symptoms or side effects. We describe the design of HealthWeaver Mobile, a mobile phone application we developed to help patients manage care-related information in such situations. We discuss findings from two participatory design groups with breast cancer patients and the design decisions made to implement functional requirements uncovered in those groups.